Prevalence of Vitamin D Deficiency and the Associated Risk Factors in Adults with Thyroid Nodule in Royal Commission Hospital, Kingdom of Saudi Arabia - Alyousif, Hussain; Alamin, Naser A; Ahmed, Mona A Sid; Saeed, Ayat Al; Hassoni, Abdulmuhsen Hussein; Aldarwish, Zahra. A.; Musa, Imad R (International Journal of Innovative Research in Medical Science, 2022)
Vitamin D is an essential nutrient for the human body. Its deficiency is linked with many common chronic diseases, types of cancer and thyroid disorders. Recent data have shown high rates of vitamin D deficiency, thyroid nodules and an increase in the incidence of thyroid cancer in the Kingdom of Saudi Arabia (KSA). We conducted this study to evaluate the rates of vitamin D deficiency and associated risk factors in patients with thyroid nodules in the Eastern Region of the KSA. Methods: A retrospective study was conducted between 1 January 2015 and 31 December 2021. The recruited patients had documented thyroid nodules based on the American College of Radiology’s Thyroid Imaging Reporting and Data System (TI-RADS). Results: There were 391 patients with thyroid nodules enrolled in the study. The median (interquartile range [IQR]) age was 46.00 (20.0) years, and 332 (84.9%) of the participants were women. The patients’ median (IQR) body mass index was 30.26 (7.71) kg/m2, and the median (IQR) 25-hydroxyvitamin D (25[OH)]D) level was 14.50 (12.0) nmol/L. There was a high prevalence (89.8%) of vitamin D deficiency among patients with thyroid nodules. In the univariate analysis, there were significant associations between 25(OH)D level and age, hypertension, hyperthyroidism, thyroid-stimulating hormone level, free triiodothyronine level and thyroid ultrasound-based TI-RADS scores of 3 to 5. In the multivariate analysis, age, free thyroxine level, free triiodothyronine level and hyperthyroidism were not significantly associated with 25(OH)D level. However, there were significant associations between 25(OH)D level and hypertension (odds ratio [OR]=0.438, 95% confidence interval [CI] 0.210‒0.911) and higher TI-RADS scores (TI-RADS 4: OR=9.654 [95% CI 1.819‒51.226] and TI-RADS 5: OR=7.784 [95% CI 1.473‒41.135]). Conclusion: There was a high prevalence of vitamin D deficiency among patients with nodular thyroid disease. TI-RADS ultrasound scores of 4 and 5 and the presence of hypertension were significantly associated with lower levels of vitamin D.